1997
DOI: 10.1093/rheumatology/36.10.1100
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective review of yttrium-90 synovectomy in the treatment of knee arthritis

Abstract: We reviewed the case notes and X-rays of all patients with knee arthritis treated with yttrium-90 for the first time at a single institution from November 1981 to November 1995. Outcomes were assessed as 'improved' or 'not improved' by review of the case notes at 3, 6 and 12 months, and by the absence of further intra-articular (IA) steroid injections. Of the 121 knees treated, 87 had adequate follow-up information to allow an assessment of outcomes. Overall, 46% (95% CI 36-57) were improved at 12 months and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1
4

Year Published

2000
2000
2015
2015

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 16 publications
0
21
1
4
Order By: Relevance
“…The use of radiosynovectomy in osteoarthritis is rather more controversial. A New Zealand study showed that while yttrium-90 radiosynovectomy was safe and moderately effective in infl ammatory arthritides of the knee, it was of little benefi t in established OA, or in patients with secondary OA changes on X-rays [ 83 ]. A German study showed good or excellent improvement in clinical symptoms in 40 % of 35 patients with therapy-resistant joint effusions caused by severe OA [ 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of radiosynovectomy in osteoarthritis is rather more controversial. A New Zealand study showed that while yttrium-90 radiosynovectomy was safe and moderately effective in infl ammatory arthritides of the knee, it was of little benefi t in established OA, or in patients with secondary OA changes on X-rays [ 83 ]. A German study showed good or excellent improvement in clinical symptoms in 40 % of 35 patients with therapy-resistant joint effusions caused by severe OA [ 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…In some cases it is advantageous to keep radioactivity for therapeutical purposes in the site into which it was injected; such applications include above all radiosynovectomy (application of radioactivity into synovial space of the inflammated joint to suppress inflammation) [28][29][30] and brachytherapy (local radiotherapy of solid tumor by an implanted emitter) [31,32].…”
Section: Local Applications Of Nanoparticlesmentioning
confidence: 99%
“…For radiosynovectomies [28][29][30], nanoparticles posses two significant advantages: they keep the radionuclide in the synovial space because of hindered diffusion due to their size and they are internalized by macrophages. Macrophages are the main cause of symptoms of inflammation, so when cytotoxic radioactivity is concentrated inside them, it has beneficial antiinflammatory effects.…”
Section: Local Applications Of Nanoparticlesmentioning
confidence: 99%
See 2 more Smart Citations